Economy of the pribumi in late colonial Java 1900-1942 C.E. : continuity and change in Priangan - Alwi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Priangan residency was situated in the south-western part of Java. The economy of its population was somewhat better compared to those of Central and East Java due to different policies and different kinds of compulsory crops implemented by the colonial rule in the region. The introduction of the Ethical Policy in 1900 had given more opportunities to the natives of Priangan as well as to those living in the other regions, in terms of enhancing their economy and welfare. This study discusses the economic policy of the colonial government in Priangan, West Java from 1900 to 1942 and how it affected the native society. It also examines how the natives of Priangan responded to the new economic challenges, whether they were able to get benefit from the Ethical Policy and whether or not their welfare was improved by it. The result of this study shows that the economic activities of the native society in Priangan during the Ethical Period had expanded significantly from agriculture to industry and commerce, particularly in the field of textile, cigarette, crafts and bank cooperative. Even in agriculture, some native farmers were able to work together and established cooperative enterprises. The time period of this study also witnessed the emergence of a number of native entrepreneurs in Priangan. However, the study also finds that there was no structural change up to the end of the colonial period regarding the economic stratification in the Netherlands East Indies. Despite its improved economic condition, the natives remained at the bottom of the socio-economic level as they had previously been.